Tales of mystery and imagination Collins Classics - Poe, Edgar Allan (London : Harper Collins Publishers, 2011)
This classic collection brings together some of Edgar Allan Poe$1 (Bs most celebrated tales of horror, suspense, and the macabre. Blending mystery with gothic atmosphere, the stories explore themes of death, madness, obsession, and the supernatural. Featuring famous works like The Tell-Tale Heart, The Fall of the House of Usher, and The Pit and the Pendulum, Poe$1 (Bs vivid prose and psychological depth continue to captivate readers, making this volume a cornerstone of classic horror literature.s
Keywords: English - Fiction Book